The Leadership Crisis In The Medium-Sized Business Sector Is Facing A Endemic To Adapt Information Technology ; Case Study SME Entrepreneur Kelurahan Padasuka Bandung Regency - Sugiana, Neng Susi Susilawati; Maisa, Asmara Azizah; Dirgantari, Puspo Dewi (Operations Research: International Conference Series, 2023)
Developing a business is a manifestation of growth activities that will be the key to success in going through the continuity of a business. It becomes the basic basis for making decisions that are important for company policy in good situations or in unpredictable situations such as the covid 19 pandemic. A leader in a medium-sized business of course pays attention to all aspects of support that make the decision device taken by paying attention to reactions occurring both internally and in the market. You will see the character of a leader who is ready to face a crisis, especially in adapting information technology as part of the relocation of businesses to digital caused by the difficulty of penetrating the market directly. Researching how many medium-sized business owners in Bandung are adapting the use of information technology as a means of business in 2020-2022. As a result of the leadership crisis, it is feared that it can have an impact on the running of the business by analyzing qualitatively that the behavior of an agile leader will have an impact on the use of information technology in their business. For that it can be seen how much a leader is able to adapt or in other words he is able to accept changes quickly and apply them in his business. For this reason, this research is expected to be a reference tool in terms of leadership characteristics in dealing with crises due to the pandemic or post-Covid-19 pandemic.